Monolithic integration of Bi-based organic-inorganic perovskite single crystal film
Through the monolithic integration technology of Bi-based organic-inorganic perovskite single crystal thin film, single crystal thin films are grown using the space-limiting method, which solves the interface defects and toxicity problems of lead-based materials in existing photodetectors, and achieves high performance, Stable photodetector.
Patent Information
- Application Number
- CN202411388761.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-07
AI Technical Summary
The design of multi-layer structures in existing photodetectors leads to an increase in interface defects, affecting the photogenerated carrier transport capacity, reducing device performance, and lead-based perovskite materials are limited due to toxicity and instability.
Using the monolithic integration technology of Bi-based organic-inorganic perovskite single crystal thin film, single crystal thin film is grown through the space-limiting method to form a 3D perovskite structure similar to the lead-based structure, and obtain phase-stable and low exciton binding energy. The organic-inorganic hybrid perovskite single crystal thin film.
It reduces interface defects, improves photogenerated carrier transport capability, improves the performance and stability of the photodetector, and avoids the risk of lead toxicity.
Smart Images

Figure CN119392347A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of non-lead-based perovskite two-dimensional single crystal thin films, and in particular to monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films. Background Art
[0002] The photoelectric effect has given rise to photoelectric detection technology that can convert light signals into electrical signals. Photodetectors are optoelectronic devices that convert light signals into current signals that can be further processed or stored based on the principle of the photoelectric effect. Based on the different wavelengths of the incident light, photodetectors can achieve photocurrent responses in the ultraviolet spectrum range, visible spectrum range, near-infrared spectrum range and infrared spectrum range, respectively. Based on this, they are widely used in scientific research fields such as astronomical observation, medical diagnosis, and environmental monitoring. Self-powered photodetectors have the characteristic of not requiring additional voltage, which means that the energy consumption of optoelectronic devices is greatly reduced. A large number of previous studies mainly achieved the self-powered characteristics of photodetectors by designing multilayer heterostructures. On the one hand, the design of multilayer structures is not only complicated in preparation process. On the other hand, multilayer structures lead to an increase in interface defects, thereby affecting the transport of photogenerated carriers and reducing the performance of optoelectronic devices. Therefore, self-powered photodetectors with a single-layer structure are expected to reduce interface defects, promote the transport capacity of photogenerated carriers, and improve the performance of photodetectors. Among them, the preparation of a single-layer optoelectronic functional material is a key factor.
[0003] Organic-inorganic hybrid perovskite materials have unique optoelectronic properties such as tunable band gap, high absorption coefficient, high fluorescence quantum yield, and excellent photoelectric conversion efficiency. Therefore, they have been widely used in optoelectronic devices such as field effect transistors and solar cells in recent years. At present, organic-inorganic hybrid perovskites used to construct optoelectronic devices mainly focus on the preparation of polycrystalline films by spin coating. Studies have shown that defect states exist at the grain boundaries and surfaces of perovskites. Although organic-inorganic hybrid perovskite polycrystalline films also exhibit relatively good photoelectric effects, polycrystalline films are composed of irregular grains, which indicates that there are a large number of grain boundaries and defect state densities in perovskite polycrystalline films, resulting in serious carrier capture and higher dark current, which are not conducive to the performance stability of optoelectronic devices. Compared with polycrystalline materials, perovskite single crystal materials are more stable in the ambient atmosphere and show better carrier transport characteristics and stability. The growth of perovskite single crystal materials is difficult, mainly because the nucleation and growth processes are difficult to control. Compared with vapor phase epitaxial growth and cavitation-induced asymmetric crystallization, the spatial confinement method has mild growth conditions and is not limited by the operating environment and large equipment. This will provide technical support for the preparation of high-quality perovskite single crystal films.
[0004] The research on perovskite materials is currently focused on Pb-based materials. However, in practical applications, they are limited by lead toxicity and inherent instability (such as sensitivity to environmental factors such as water, heat, and light). Traditional research has mainly focused on isovalent substitution. Sn and Ge elements can meet the coordination requirements and maintain charge balance, effectively avoiding excessive lattice distortion caused by element substitution, thereby preparing non-lead-based perovskite traditional substitution elements. In the study of heterovalent substitution, the structural formula of M(Ⅲ)-based perovskite A3B(Ⅲ)2X9 is equivalent to removing 1 / 3 of the B-site cations in ABX3. Among them, A3B(III)2X9 compounds have two typical structures, one is isolated face sharing [B2X9] 3- The octahedrons form a 0D dimer, and the other is a 2D layered perovskite. The formation of the two structures depends on the different choices of A, B and X ions. 3+ Cations have similar ns 2 The electronic configuration, electronegativity, and ionic radius comparable to those of Pb are expected to be used to prepare high-performance lead-free perovskites. However, the substitution of trivalent cations will reduce the structural dimension of the perovskite, resulting in lower band dispersion, increased effective carrier mass, and reduced carrier migration efficiency. Summary of the invention
[0005] The purpose of the present invention is to utilize halide double perovskites substituted by organic cations and mixed metal ions M(I) and M(III) to form a 3D perovskite structure that is very similar to the lead-based structure, and to obtain monolithic integration of phase-stable, low exciton binding energy organic-inorganic hybrid perovskite single crystal films.
[0006] To achieve the above-mentioned purpose, the present invention proposes a monolithic integration of a Bi-based organic-inorganic perovskite single crystal film, which grows a single crystal film based on a spatial confinement method and monolithically integrates a lead-free halide perovskite single crystal film with a substrate; the perovskite structure of the lead-free halide perovskite single crystal film is A3Bi2X9.
[0007] The specific steps include:
[0008] S1: preparing a stable Bi-based organic-inorganic perovskite precursor solution;
[0009] S1.1: Mix two solvents, N-N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), at room temperature in a certain volume ratio to obtain a uniform and transparent mixed solvent for later use;
[0010] S1.2: Based on the perovskite structure of A3Bi2X9, select different halogenated organic salt precursors and halogenated metal salt precursors, weigh them according to the stoichiometric molar ratio, add them to the mixed solvent obtained in S1.1, adjust the heating temperature and stir continuously until the precursors are dissolved;
[0011] S1.3: Filter out the precipitate in the precursor saturated solution obtained in S1.2 to obtain a clear Bi-based organic-inorganic hybrid perovskite precursor saturated solution for later use.
[0012] S2: The Bi-based organic-inorganic perovskite precursor solution is sandwiched between the hydrophobic treated substrate and the bottom electrode substrate to grow, thereby obtaining a monolithically integrated Bi-based organic-inorganic hybrid perovskite single crystal film.
[0013] S2.1: n-hexane and octadecyltrichlorosilane (OTS) are mixed according to a certain volume ratio, and stirred at room temperature to form a uniform transparent solution, which is used as a solvent for substrate hydrophobic treatment and set aside;
[0014] S2.2: Wash the substrates of different sizes required for the experiment, blow dry them with nitrogen gas and set aside;
[0015] S2.3: Take several clean substrates and immerse them in the hydrophobic solvent prepared in step S2.1 for a certain period of time to perform hydrophobic treatment; then, wash the hydrophobic treated substrates, wipe off the residual impurities on the surface, blow dry with nitrogen gas, and set aside;
[0016] S2.4: Take a certain volume of the saturated precursor solution obtained in step S1 and drip it onto the surface of the substrate treated with hydrophobicity in step S2.3; then, take a clean bottom electrode substrate as a growth substrate for the organic-inorganic hybrid perovskite single crystal thin film, and laminate it with the substrate with the saturated solution to form a sandwich structure, ensuring that the liquid film in the confined space is evenly spread;
[0017] S2.5: Clamp the two substrates with a clamp, place them in an oven, adjust the growth temperature and time, evaporate the saturated solvent, and obtain a monolithic integrated Bi-based organic-inorganic hybrid perovskite single crystal film.
[0018] Preferably, in S1.2, the organic halide salt at the A position in A3Bi2X9 is selected from: methylamine hydroiodide (MAI), formamidine hydroiodide (FAI), methylamine hydrobromide (MABr) or formamidine hydrobromide (FABr); the inorganic halide metal salt is selected from: cesium iodide (CsI) and cesium bromide (CsBr);
[0019] The stoichiometric molar ratio of the halogenated organic salt and the halogenated metal salt at the A position is: the sum is equal to 3; the inorganic halogenated metal salt at the B position is selected as: bismuth iodide (BiI3).
[0020] Preferably, in said S1.1, the volume ratio of NMN dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) is in the range of: (1-10): (0.1-5).
[0021] Preferably, the temperature range of the precursor solution placed on the hot plate for heating in S1.2 is 25°C-80°C.
[0022] Preferably, the filtration in S1.3 uses a PTFE organic phase with a specification of 0.22 μm.
[0023] Preferably, in S2.1, the volume ratio of n-hexane to octadecyltrichlorosilane (OTS) is in the range of (1000-100):(1-0.2).
[0024] Preferably, in S2.2: ultrasonically clean different substrates of a certain size required for the experiment using acetone, deionized water and ethanol in sequence, and blow dry them with nitrogen for later use.
[0025] Substrate selection: glass, quartz or mica; substrate size range: 5mm-500mm.
[0026] In S2.4, the bottom electrode substrate is selected from: ITO, FTO or graphene; the hydrophobic treatment substrate is selected from: glass, quartz, mica. The size range of the substrate is: 5mm-500mm.
[0027] Preferably, in S2.3, the hydrophobic treated glass substrate is ultrasonically cleaned using n-hexane, chloroform and isopropanol in sequence to remove residual impurities on the surface, and then dried with nitrogen for later use.
[0028] Preferably, in S2.5, the growth temperature control range is: 30°C-100°C; the growth time range is: 6h-180h.
[0029] Compared with the prior art, the advantages of the present invention are:
[0030] 1. The present invention utilizes halide double perovskites substituted by organic cations and mixed metal ions M(I) and M(III) to form a 3D perovskite structure that is very similar to a lead-based structure, thereby obtaining a phase-stable, low exciton binding energy organic-inorganic hybrid perovskite single crystal film.
[0031] 2. The present invention adopts the spatial confinement method to grow single crystal thin films, which is independent of specific substrates and strict lattice matching, which will be conducive to the monolithic integration of lead-free halide perovskite single crystal thin films and required substrates. Monolithic integration can not only simplify the device structure, but also expand new optoelectronic applications by utilizing complementary characteristics. This will help reduce costs and provide the possibility for the preparation of large-area single crystal thin film-based photodetectors.
[0032] 3. Bi-based organic-inorganic hybrid perovskite single crystals are integrated on the surface of the bottom electrode substrate as optoelectronic functional materials. After being applied to perovskite photodetectors, Au is used as the top electrode to design a vertical device structure with asymmetric electrodes. The constructed perovskite photodetector can exhibit a wide spectral detection range at 0V bias, showing self-powered characteristics, as well as excellent performance in responsivity and detection rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an atomic force microscope image (AFM image) of the MCBIB perovskite single crystal film prepared in Example 1;
[0034] Figure 2 The photoelectric performance of the Au / MCBIB / ITO photodetector with a wide spectrum as described in Example 2: IV curve;
[0035] Figure 3 The photoelectric performance of the Au / MCBIB / ITO photodetector with a wide spectrum as described in Example 2: It curve;
[0036] Figure 4 This is the photoelectric performance of the Au / MCBIBITO photodetector with a wide spectrum as described in Example 2: response and detection rate curve. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further described below.
[0038] The drugs required for the experiment are as follows:
[0039] Methyl hydrobromide (MABr, analytical grade), cesium iodide (CsI, analytical grade), bismuth iodide (BiI3, analytical grade), N-N-dimethylformamide (analytical grade), dimethyl sulfoxide (analytical grade), isopropanol (analytical grade), n-hexane (analytical grade), octadecyltrichlorosilane (OTS) (analytical grade), and acetone (analytical grade) were purchased from Aladdin Reagent Company; ethanol (analytical grade) was purchased from China National Pharmaceutical Group Shanghai Reagent Company, and deionized water.
[0040] Example 1: Monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films:
[0041] (1) The total volume of the mixed solvent is 1 mL, wherein N-N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are mixed in a volume ratio of 4:1 and stirred at room temperature to obtain a uniform and transparent mixed solvent;
[0042] (2) With A3B2X9 as the basic structural formula of perovskite, methyl hydrobromide (MABr) and cesium iodide (CsI) are added according to the stoichiometric molar ratio of x:y=2:1; then, a certain mass of bismuth iodide (BiI3) is weighed according to the stoichiometric molar ratio; the precursor is added to the mixed solvent in step (1), and the mixture is heated and stirred on a hot plate at 50°C until the solid is dissolved.
[0043] (3) Subsequently, the precursor saturated solution of step (2) was filtered using a 0.22 μm PTFE organic phase filter to obtain a clarified precursor saturated solution.
[0044] (4) Preparation of hydrophobic solvent: n-hexane and octadecyltrichlorosilane (OTS) were mixed in a volume ratio of 500:1, and stirred at room temperature to form a uniform transparent solution for later use.
[0045] (5) Cut the ITO substrate and the glass substrate into a size of 120 mm x 120 mm for single crystal thin film integration; then, ultrasonically clean the determined substrates with acetone, deionized water, and ethanol in turn for later use;
[0046] (6) The clean glass substrate was immersed in the hydrophobic solvent of step (4) for 24 hours for hydrophobic treatment. Subsequently, the OTS-modified glass substrate was ultrasonically cleaned with n-hexane, chloroform, and isopropanol in sequence, and the residual impurities on the surface were wiped off with dust-free paper, and the substrate was dried with nitrogen gas for later use.
[0047] (7) Take a clean glass substrate and drop 1 μL of a saturated solution of a perovskite precursor on its surface. Then, fit it tightly to a clean ITO substrate and clamp the two substrates with two clamps to spread the liquid film evenly in the confined space. The sample is placed in an oven, the growth temperature is set to 70°C, and the growth time is 24 hours to obtain a Bi-based organic-inorganic perovskite single crystal film (MA2CsBi2I7Br2) integrated on an ITO substrate.
[0048] The Bi-based organic-inorganic perovskite single crystal film prepared in Example 1 is as follows Figure 1 As shown in the atomic force microscope image (AFM image), it can be clearly observed that the surface of the single crystal film is relatively flat and dense, and the Au electrode is evenly covered on the surface of the single crystal film, which will be conducive to the transmission of charges.
[0049] Embodiment 2:
[0050] Based on the MA2CsBi2I7Br2 single crystal thin film (MCBIB) prepared in Example 1, a photodetector with self-powered characteristics and wide spectral response is constructed.
[0051] The array pattern mask is laminated to the monolithic integrated perovskite film obtained in step (2.5), and Au is used as the electrode material to construct the top electrode array by vacuum thermal deposition technology. The photodetector uses the Keithley 4200 semiconductor probe system to measure the IV curve, It curve and other data of the sample to characterize the photoelectric characteristics of the detector. Figure 2 The IV curve of the Au / MCBIB / ITO photodetector constructed with Au as the top electrode and ITO as the bottom electrode is shown. As shown in the figure, the Au / MCBIB / ITO device has a low dark current and can achieve photocurrent response in the ultraviolet and visible light bands. The switching ratio of the initial photocurrent to the dark current is I p / I d Close to 2.3×10 2 Magnitude. Figure 3 The It curve of Au / MCBIB / ITO device under 0V bias and 400nm incident light is shown. The photocurrent does not decay significantly after several switching cycles. The switching ratio I on / I off Close to 2.2×10 2 This indicates that the device exhibits good self-powered characteristics. Subsequently, the responsivity and detectivity curves of the Au / MCBIB / ITO device at 0V bias voltage show that the device responds to wavelengths from the ultraviolet band to the visible light band, with the best responsivity and detectivity at 410nm (e.g. Figure 4 This indicates that the Au / MCBIB / ITO photodetector exhibits self-powered characteristics and wide-spectrum photoresponse, which provides the possibility for the design of low-power photodetectors.
[0052] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.
Claims
1. A monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films, characterized in that: Based on the spatial confinement method to grow a single crystal film, the lead-free halide perovskite single crystal film is monolithically integrated with a substrate; the perovskite structural formula of the lead-free halide perovskite single crystal film is A3Bi2X9.
2. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 1, characterized in that: The integrated approach includes the following steps: S1: preparing a stable Bi-based organic-inorganic perovskite precursor solution; S2: The Bi-based organic-inorganic perovskite precursor solution is sandwiched between the hydrophobic treated substrate and the bottom electrode substrate to grow, thereby obtaining a monolithically integrated Bi-based organic-inorganic hybrid perovskite single crystal film.
3. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 1, characterized in that: The S1 comprises the following steps: S1.1: Mix two solvents, N-N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), at room temperature in a certain volume ratio to obtain a uniform and transparent mixed solvent for later use; S1.2: Based on the perovskite structure of A3Bi2X9, select different halogenated organic salt precursors and halogenated metal salt precursors, weigh them according to the stoichiometric molar ratio, add them to the mixed solvent obtained in S1.1, adjust the heating temperature and stir continuously until the precursors are dissolved; S1.3: Filter out the precipitate in the precursor saturated solution obtained in S1.2 to obtain a clear Bi-based organic-inorganic hybrid perovskite precursor saturated solution for later use.
4. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 3, characterized in that: In S1.2, the organic halide salt at the A position in A3Bi2X9 is selected from methylamine hydroiodide (MAI), formamidine hydroiodide (FAI), methylamine hydrobromide (MABr) or formamidine hydrobromide (FABr); the inorganic halide metal salt is selected from cesium iodide (CsI) and cesium bromide (CsBr); The stoichiometric molar ratio of the halogenated organic salt and the halogenated metal salt at the A position is: the sum is equal to 3; the inorganic halogenated metal salt at the B position is selected as: bismuth iodide (BiI3).
5. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 3, characterized in that: In the S1.1, the volume ratio of NMN dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) is in the range of: (1-10): (0.1-5).
6. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 2, characterized in that: The S2 comprises the following steps: S2.1: n-hexane and octadecyltrichlorosilane (OTS) are mixed according to a certain volume ratio, and stirred at room temperature to form a uniform transparent solution, which is used as a solvent for substrate hydrophobic treatment and set aside; S2.2: Wash the substrates of different sizes required for the experiment, blow dry them with nitrogen gas and set aside; S2.3: Take several clean substrates and immerse them in the hydrophobic solvent prepared in step S2.1 for a certain period of time to perform hydrophobic treatment; then, wash the hydrophobic treated substrates, wipe off the residual impurities on the surface, blow dry with nitrogen gas, and set aside; S2.4: Take a certain volume of the saturated precursor solution obtained in step S1 and drip it onto the surface of the substrate treated with hydrophobicity in step S2.3; then, take a clean bottom electrode substrate as a growth substrate for the organic-inorganic hybrid perovskite single crystal thin film, and laminate it with the substrate with the saturated solution to form a sandwich structure, ensuring that the liquid film in the confined space is evenly spread; S2.5: Clamp the two substrates with a clamp, place them in an oven, adjust the growth temperature and time, evaporate the saturated solvent, and obtain a monolithic integrated Bi-based organic-inorganic hybrid perovskite single crystal film.
7. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 6, characterized in that: In S2.1, the volume ratio of n-hexane to octadecyltrichlorosilane (OTS) is in the range of (1000-100):(1-0.2).
8. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 6, characterized in that: In S2.2: substrate selection: glass, quartz or mica; substrate size range: 5mm-500mm; In S2.4, the bottom electrode substrate is selected from: ITO, FTO or graphene; the hydrophobic treatment substrate is selected from: glass, quartz, mica. The size range of the substrate is: 5mm-500mm.
9. The monolithic integration of Bi-based organic-inorganic perovskite single crystal thin films according to claim 6, characterized in that: In S2.5, the growth temperature control range is: 30℃-100℃; the growth time range is: 6h-180h.
Citation Information
Patent Citations
Growth method of halide perovskite thin single crystal
CN116427011A
Bi-based perovskite thin film crystal phase preparation method and application
CN116621881A
Perovskite heterojunction for direct X-ray detector and construction method thereof
CN116634826A
Perovskite film production method, perovskite film, solar battery and perovskite film forming solvent
WO2017170869A1